Design and designing : a critical introduction - Evans, Chris , 1947-; Garner, Steve W. [ (Steven William)] (Berg Publishers, 2012)
"Design and Designing will provide the reader with a very broad and critical understanding of what is essentially a practical subject. Designing today is less a craft and more a part of the knowledge economy. It's all about knowing how to acquire knowledge and how to apply it creatively. Design and Designing covers the design process, modeling and drawing, working with clients, production and consumption, sustainability, professional practice and design futures. Chapters are written by expert teachers and practitioners from around the globe, each presenting an accessible and engaging insight into their field of deisgn. Chapters are illustrated with a wide range of images and information boxes, which extend or highlight key material. Each section concludes with a design project, a hands-on activity for the reader. Design and Designing covers the full range of the subject from graphic communication, to product design, to fashion and games design, setting all in their aesthetic, ethical and social contexts. The aim is for the reader to learn from today's best practice and best thinking, to develop a critical sense, to become the designers of tomorrow"